2005
DOI: 10.1084/jem.20041542
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ immunodominance among Epstein-Barr virus lytic cycle antigens directly reflects the efficiency of antigen presentation in lytically infected cells

Abstract: Antigen immunodominance is an unexplained feature of CD8+ T cell responses to herpesviruses, which are agents whose lytic replication involves the sequential expression of immediate early (IE), early (E), and late (L) proteins. Here, we analyze the primary CD8 response to Epstein-Barr virus (EBV) infection for reactivity to 2 IE proteins, 11 representative E proteins, and 10 representative L proteins, across a range of HLA backgrounds. Responses were consistently skewed toward epitopes in IE and a subset of E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(187 citation statements)
references
References 54 publications
13
172
0
2
Order By: Relevance
“…Indeed from recent work, this also seems to be true of exogenously acquired EBV lytic cycle Ags. Thus, coculture between appropriate mixtures of semipermissive HLAmismatched (donor) and nonpermissive HLA-matched (recipient) LCL never led to recognition by lytic epitope-specific CD8 ϩ T cells (53). By contrast, the recognition of semipermissive LCL cells by virus-structural Ag-specific CD4 ϩ T cells was found to be dependent upon the intercellular transfer of virions within the culture (54).…”
Section: Discussionmentioning
confidence: 90%
“…Indeed from recent work, this also seems to be true of exogenously acquired EBV lytic cycle Ags. Thus, coculture between appropriate mixtures of semipermissive HLAmismatched (donor) and nonpermissive HLA-matched (recipient) LCL never led to recognition by lytic epitope-specific CD8 ϩ T cells (53). By contrast, the recognition of semipermissive LCL cells by virus-structural Ag-specific CD4 ϩ T cells was found to be dependent upon the intercellular transfer of virions within the culture (54).…”
Section: Discussionmentioning
confidence: 90%
“…Strong CD8 ϩ T cell responses to the tegument phosphoprotein 65 and the immediate early protein 1 were found for the ␤-herpesvirus human CMV (24,25). In healthy carriers of the ␥-herpesvirus EBV, a considerable proportion of the peripheral T cell repertoire is directed against EBV-encoded Ags, predominantly derived from latent and immediate early viral proteins (26). Thus, despite the presence of a fully competent immune system mounting a powerful response against herpesvirus infections, these viruses fail to be eliminated.…”
Section: Ajor Histocompatibility Complex Class I-mediated Peptide Pmentioning
confidence: 96%
“…The latter responses can be numerically dominant and are directed, in the case of CD4 ϩ T cells, mainly against reprocessed virion structural proteins 21 and, in the case of CD8 ϩ T cells, mainly against immediate early and early nonstructural proteins. 34 Using LCLs transformed with a virus deleted for BZLF1, the key initiator of EBV lytic cycle, allows one to exclude lytic cycle proteins as an antigen source. As anticipated, we found that seropositive donors mounted ex vivo CD8 responses that were stronger to the wild-type than to the BZ k/o virus-transformed LCL, whereas seronegative donors responded to neither stimulus.…”
Section: Discussionmentioning
confidence: 99%